Preparation and Anticorrosion of Octadecyl Trichlorosilane SAMs for Copper Surface - Xue Shouqing; Liu Xiaohui (International Journal of Analytical Chemistry)
The self-assembled monolayer (SAM) was prepared using octadecyl trichlorosilane (OTS) in distilled solution on the copper surface. The effect of inhibitor concentration on the rate of inhibition efficiency and corrosion rate in corrosion medium on copper by using polarization curves, electrochemical impedance spectroscopy (EIS), scanning electron microscope (SEM) was studied. The results showed that OTS SAMs exhibit the better corrosion resistance; the corrosion potential of copper OTS SAMs protection increased by about 1.02 V, while the corrosion current density decreased to 0.59 μA/cm2. The corrosion rate is minimized and flattened and can reach 9.2% while the inhibition efficiency reached 95.4%, when the corrosion inhibitor has concentration of 40 ppm.